Neuropeptide Y/Y5 Receptor Pathway Stimulates Neuroblastoma Cell Motility Through RhoA Activation - Abualsaud, Nouran; Caprio, Lindsay; Galli, Susana; Krawczyk, Ewa; Alamri, Lamia; Zhu, Shiya; Gallicano, G. Ian; Kitlinska, Joanna (Frontiers in Cell and Developmental Biology, 2021)
Neuropeptide Y (NPY) has been implicated in the regulation of cellular motility under various physiological and pathological conditions, including cancer dissemination. Yet, the exact signaling pathways leading to these effects remain unknown. In a pediatric malignancy, neuroblastoma (NB), high NPY release from tumor tissue associates with metastatic disease. Here, we have shown that NPY stimulates NB cell motility and invasiveness and acts as a chemotactic factor for NB cells. We have also identified the Y5 receptor (Y5R) as the main NPY receptor mediating these actions. In NB tissues and cell cultures, Y5R is highly expressed in migratory cells and accumulates in regions of high RhoA activity and dynamic cytoskeleton remodeling. Y5R stimulation activates RhoA and results in Y5R/RhoA-GTP interactions, as shown by pull-down and proximity ligation assays, respectively. This is the first demonstration of the role for the NPY/Y5R axis in RhoA activation and the subsequent cytoskeleton remodeling facilitating cell movement. These findings implicate Y5R as a target in anti-metastatic therapies for NB and other cancers expressing this receptor.